Development of e-Health Monitoring System for Remote Rural Community of India - Jabirullah, Mohammad; Ranjan, Rakesh; Ali Baig, Mirza Nemath; Kumar Vishwakarma, Anish (International Conference on Signal Processing and Integrated Networks (Online), 2020)
Recent advancement in healthcare technologies provides a new edge to the medical services. The health condition of the people living in remote rural areas of India is far worse than urban people. To monitor basic medical parameters for identifying the abnormalities in the early stage of chronic diseases need regular interval hospital's visit which is a relatively costly and time-consuming process. Rare availabilities of medical experts or medical centers, ignorance of the people and proper care at the correct time are the prime causes of serious medical concern which leads to unexpected death. This work is an attempt to solve basic health problems and take advice from registered medical experts for the betterment of the targeted community. The imperative goal of the paper is to develop a cost-effective and reliable Internet of Things (IoT) architecture customized health monitoring system to visualize some basic medical parameters like heartbeat rate, blood pressure and temperature of the patient. In the proposed e-Health monitoring system, the medical parameters are collected from dedicated sensors and send over the internet to the webserver through ESP8266 Wi-Fi module which is commanded by the Arduino controller. The registered medical experts can visualize and advise after analyzing the data of the patient present on the webserver. Hence, this system provides cost-effective, secure, reliable and real-time solutions for improving the health status of rural people.